POLITICAL COMMUNICATION AND PERSONAL BRANDING: A CASE STUDY OF THE CAMPAIGN OF JAKARTA DPRD CANDIDATE WILLIAM ADITYA SARANA IN THE 2024 ELECTION - Muslim, Patriot (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
This study aims to explore the effectiveness of political communication and personal branding strategies employed by William Aditya Sarana in building strong relationships with voters and shaping public perception. Utilizing social media as a primary tool, these strategies have shown positive impacts on voter support, particularly among young and urban communities. However, challenges in managing criticism and negative issues highlight the need for politicians to develop mature strategies for image management in the digital era. This research contributes to the understanding of political communication and personal branding in contemporary politics, providing insights into how young politicians can leverage these strategies for success. The findings underscore the importance of understanding the target audience, maintaining message consistency, and effectively handling criticism. While this study provides significant insights, its scope is limited to a single politician, suggesting a need for further research involving diverse subjects and methodologies.